Endotracheal Intubation by Paramedics Using Neodymium Magnet and Modified Stylet in Simulated Difficult Airway: A Prospective, Randomized, Crossover Manikin Study - Sedat Bilge; Onur Tezel; Yahya Ayhan Acar; Guclu Aydin; Attila Aydin; Gokhan Ozkan (Emergency Medicine International)
Background. The present study evaluates the success and efficacy of endotracheal intubation (ETI) using a modified intubation stylet and a magnet system to direct the stylet into the trachea. The system was developed by the researchers in an attempt to increase the success and efficacy of ETI. Methods. ETI procedures were performed on an airway management manikin by emergency medical technicians with at least four years of experience in ETI. The technicians used a stylet modified with an iron ball affixed to the tip and a neodymium magnet, designed specifically for the study. The intention was to guide the endotracheal tube into the trachea at the level of the thyroid and cricoid cartilages on the manikin with the aid of the modified stylet and the magnetic force of the neodymium magnet. The success rate, completion time, and degree of difficulty of two procedures were compared: magnetic endotracheal intubation (METI) and classic ETI (CETI). Results. The success rate was 100% in both groups. The mean completion times for the METI and CETI procedures were 18.31 ± 2.46 s and 20.01 ± 1.95 s, respectively. There were significant differences in completion time and degree of difficulty between the METI and CETI procedures (both p=0.001). Conclusions. We found the use of a neodymium magnet and modified stylet to be an effective method to guide the endotracheal tube into the trachea. The present study may provide a basis for future studies.